Prevalence and Predictors of Additional Ablation Beyond Pulmonary Vein Isolation in Patients With Paroxysmal Atrial Fibrillation - Xie, Xin; Yang, Gang; Li, Xiaorong; Yu, Jinbo; Zhang, Fengxiang; Ju, Weizhu; Chen, Hongwu; Li, Mingfang; Gu, Kai; Cheng, Dian; Wang, Xuecheng; Wu, Yizhang; et al. (Frontiers in Cardiovascular Medicine, 2021)
BACKGROUND: Pulmonary vein isolation (PVI) is an effective strategy in the treatment of paroxysmal atrial fibrillation (PAF). Yet, there are limited data on additional ablation beyond PVI. In this study, we sought to assess the prevalence, predictors, and outcomes of additional ablation in PAF patients. METHODS: A total of 537 consecutive patients with PAF were retrospectively evaluated for the index procedure. PVI was successfully conducted in all patients, after which electrophysiological study and drug provocation were performed, and additional ablations were delivered for concomitant arrhythmias, non-PV triggers, and low voltage zone (LVZ). The prevalence, predictors, and outcomes of additional ablation were analyzed. RESULTS: Among 537 consecutive patients, 372 addition ablations were performed in 241 (44.88%) patients, including 252 (67.74%) concomitant arrhythmias in 198 (36.87%) patients, 56(15.05%) non-PV triggers in 52 (9.68%) patients and 64(17.20%) LVZ modification in 47(8.75%) patients. Lower LVEF (OR =0.937, p = 0.015), AF episode before procedure (OR =2.990, p = 0.001), AF episode during procedure (OR =1.998, p = 0.002) and AF episode induced after PVI (OR =15.958, p < 0.001) were independent predictors of additional ablation. Single-procedure free from atrial arrhythmias at 58.36 ± 7.12 months post-ablation was 70.48%. CONCLUSIONS: Additional ablations were common in patients with PAF for index procedure. Lower LVEF and AF episodes before, during the procedure, and induced after PVI may predicts additional ablation.